Pemanfaatan Tanaman Putat Sebagai Teh Fungsional dalam Mendukung Desa Ekowisata Danau Tangkas Desa Tanjung Lanjut - Indra Lasmana Tarigan; Bambang Hariyadi; Putri Pebridayanti; Madyawati Latief (Universitas Mathla'ul Anwar Banten, 2022)
UTILIZATION OF PUTAT PLANTS AS FUNCTIONAL TEA IN SUPPORTING THE DANAU TANGKAS ECOTOURİSM VİLLAGE, TANJUNG LANJUT VILLAGE.Tangkas Lake has an area of 403 hectares and around the lake, there are thousands of putat trees (Planchonia valida) which have not been explored and utilized optimally by residents. Utilization of Putat which is still very minimal in the community, especially to encourage edutourism at Tangkas Lake. Putat's potential needs to be developed by providing education to the public so that they can process Putat as a functional product, as well as providing processing training. The activity began with socializing the potential of Putat Plants, training on processing Putat leaves into functional tea, and monitoring and evaluating the implementation of activities. The community gained a significant increase in knowledge related to the knowledge of potential of Putat leaf, its efficacy, bioactive compounds, and standard processing processes for the production of Putat leaves tea. In addition, the community also has the commitment to develop and continue as a creative business to support ecotourism villages.